Olanzapine pamoate for the treatment of schizophrenia – a safety evaluation. Issue 3 (3rd March 2016) - Samalin, Ludovic; Garay, Ricardo; Ameg, Ahcène; Llorca, Pierre-Michel
ABSTRACT: Introduction : Non-adherence to long-term treatment is a major issue for patients with schizophrenia and is associated with an increased risk of relapse. Long-acting injectable (LAI) antipsychotics can offer a useful option to improve adherence. Due to the type of sustained-release mechanism, olanzapine pamoate (OLAI) can differ in safety as compared with oral olanzapine. Recent safety data concerning olanzapine pamoate required an update of previous systematic reviews. Areas covered : Safety data were found in US and EU clinical trial registries, and a literature search was undertaken using the databases PubMed and EMBASE to find all relevant published studies. Where appropriate, the number needed to harm and 95% confidence interval for categorical safety outcomes were calculated. Expert opinion : The safety profile of OLAI was similar to the well-known safety profile of oral olanzapine, except for the risk of occurrence of post-injection delirium/sedation syndrome (PDSS). Olanzapine pamoate can be a choice for schizophrenic patients with a history of response to and acceptable tolerance of oral olanzapine, who have easy access to mental healthcare settings with emergency services for the treatment of PDSS. Long-term, prospective studies assessing the efficacy and safety of OLAI and head-to-head comparisons with other LAI and oral antipsychotics are needed.